Comparing Paired-Stimulus Preference Assessments With In-the-Moment Reinforcer Analysis on Skill Acquisition: A Preliminary Investigation. (March 2018) - Leaf, Justin B.; Leaf, Ronald; Leaf, Jeremy A.; Alcalay, Aditt; Ravid, Daniel; Dale, Stephanie; Kassardjian, Alyne; Tsuji, Kathleen; Taubman, Mitchell; McEachin, John; Oppenheim-Leaf, Misty L.
Today, the use of formal preference assessments, including paired-stimulus preference assessments, is widely utilized to help determine which items to use as reinforcers during intervention. A second way to determine potential reinforcers is to analyze multiple dimensions of a stimulus in the moment, a procedure known as in-the-moment reinforcer analysis. Although paired-stimulus preference assessments are widely used, there is no experimental evidence that extensive advance preference assessments actually produce higher rates of learning than in-the-moment reinforcer analysis. The present study compared rates of learning on a simple expressive labeling task when correct responses were reinforced with items selected based on extensive formal paired-preference assessments versus items selected by a teacher using in-the-moment analysis of reinforcer effects. The results indicated no clear difference in skill acquisition, but there were clear differences in terms of efficiency and maintenance.